THE EFFECT OF PRODUCT QUALITY, PRICE, PROMOTION AND QUALITY OF SERVICE ON CUSTOMER LOYALTY IN PURCHASE DECISION MEDIATION (MSME CRAFTING BAGS FROM SYNTHESIS LEATHER MATERIAL IN BOJOASRI, KALITENGAH LAMONGAN) ANALYSIS OF THE STRUCTURE METHOD (SQUARE (PLEST - Abid Muhtarom; Edie Sugiarto; Sabilar Rosyad; Moh Ma’ruf Dzawin Nadzar (SEAN Institute, 2022)
This study examines the effect of product quality, price, promotion, and service quality on customer loyalty of MSME Leather Handicraft Bags and purchasing decisions on customer loyalty. This research is quantitative descriptive. This research involves MSME customers of leather bags. This study took a sample of 150 people. SEM with Smart PLS 3.3.7 was used to analyze. According to the research, purchasing decisions are included in partial and full mediation, and product quality, price, and promotion have a positive and significant effect on customer loyalty, while service quality has a positive but not significant effect. Product quality, price, promotion, and service quality have an effect on purchasing decisions and customer loyalty at UMKM Handicraft Bags from Synthetic Leather in Bojoasri Kalitengah Lamongan